MicroRNA-124 inhibits the progression of adjuvant-induced arthritis in rats. Issue 3 (16th January 2015) - Nakamachi, Yuji; Ohnuma, Kenichiro; Uto, Kenichi; Noguchi, Yoriko; Saegusa, Jun; Kawano, Seiji
Abstract : Objective: MicroRNAs (miRNAs) are small endogenous, non-coding RNAs that act as post-transcriptional regulators. We analysed the in vivo effect of miRNA-124 (miR-124, the rat analogue of human miR-124a) on adjuvant-induced arthritis (AIA) in rats. Methods: AIA was induced in Lewis rats by injecting incomplete Freund's adjuvant with heat-killed Mycobacterium tuberculosis . Precursor (pre)-miR-124 was injected into the right hind ankle on day 9. Morphological changes in the ankle joint were assessed by micro-CT and histopathology. Cytokine expression was examined by western blotting and real-time RT-PCR. The effect of miR-124 on predicted target messenger RNAs (mRNAs) was examined by luciferase reporter assays. The effect of pre-miR-124 or pre-miR-124a on the differentiation of human osteoclasts was examined by tartrate-resistant acid phosphatase staining. Results: We found that miR-124 suppressed AIA in rats, as demonstrated by decreased synoviocyte proliferation, leucocyte infiltration and cartilage or bone destruction. Osteoclast counts and expression level of receptor activator of the nuclear factor κB ligand (RANKL), integrin β1 (ITGB1) and nuclear factor of activated T cells cytoplasmic 1 (NFATc1) were reduced in AIA rats treated with pre-miR-124. Luciferase analysis showed that miR-124 directly targeted the 3′UTR of the rat NFATc1, ITGB1, specificity protein 1 and CCAAT/enhancer-binding protein α mRNAs. Pre-miR-124 also suppressed NFATc1 expression in RAW264.7 cells. Both miR-124 and miR-124a directly targeted the 3′-UTR of human NFATc1 mRNA, and both pre-miR-124 and pre-miR-124a suppressed the differentiation of human osteoclasts. Conclusions: We found that miR-124 ameliorated AIA by suppressing critical prerequisites for arthritis development, such as RANKL and NFATc1. Thus, miR-124a is a candidate for therapeutic use for human rheumatoid arthritis.